Tako-tsubo Syndrome as First Manifestation in a Case of Pheochromocytoma Developed From a Non-functional Adrenal Incidentaloma - Falcetta, Pierpaolo; Orsolini, Francesca; Molinaro, Eleonora; Vitti, Paolo; Tonacchera, Massimo (Frontiers in Endocrinology, 2020)
Background: Pheochromocytoma is a catecholamine secreting tumor that, in extremely rare cases, may develop over time from a non-functional adrenal adenoma. Catecholamine excess can lead to a kind of cardiomyopathy similar to that seen in tako-tsubo syndrome (TTS). Case report: A 69-years old female with a history of type 2 diabetes, hypertension, and a non-functional right adrenal adenoma diagnosed 3 years earlier was referred to our center for further investigations. During the evaluation, she had a hypertensive crisis with chest pain, tachycardia, and diaphoresis. Suspecting an acute coronary syndrome, she underwent coronary angiography, which showed the typical features of TTS. The high 24h-urinary metanephrines excretion and abdominal MRI findings were suggestive of pheochromocytoma. Right laparoscopic adrenalectomy was performed, with the resolution of all symptoms. Pathology findings confirmed the diagnosis of pheochromocytoma. After 12 months, the patient was still asymptomatic, with the echocardiography displaying a complete recovery of the left-ventricular function. Conclusions: The development of a pheochromocytoma from an adrenal non-functional adenoma is an extremely rare event, but potentially life-threating because of the catecholamine-associated cardiovascular toxicity. In particular, TTS is a form of cardiomyopathy that has been increasingly described as associated with catecholamine-secreting tumors. The exclusion of pheochromocytoma in a patient with TTS has important therapeutic implications, since the administration of β-blockers may be extremely harmful in patients with catecholamine surge in the absence of adequate α-blockage.